Telangiectatic osteosarcoma of the thoracic vertebra: a case report and literature review - Wang, Chen; Fan, Xirong; Zhang, Kai; Xue, Wen; Li, Guoquan; Wang, Qilong; Gou, Fadong; Zhou, Yi; Xing, Wenbo; Wang, Chenjian (Frontiers in Oncology, 2025)
Telangiectatic osteosarcoma (TOS) is a rare high-grade malignant tumour found primarily in the metaphysis of long bones, but can also occur in the pelvis, spine and skull. Characterized by extensive vascular dilatation and aggressive behavior, TOS often has a poor prognosis and may be misdiagnosed due to similarities with other lesions. This report presents a case of TOS of the thoracic vertebrae and reviews the relevant literature to enhance clinical awareness. A 44-year-old woman presented with chest and back pain of worsening over two months, accompanied by lower limb numbness and incomplete paralysis. Initial treatment for “low back pain” proved ineffective. Imaging showed osteolytic destruction at T10, which led to surgery, and the tumour was classified as Tomita type III. The tumour was surgically resected, showing vascular proliferation and malignant stromal cells, confirming the pathological diagnosis of TOS. However, she developed complications requiring further surgery for recurrent problems, where a hematoma was discovered. Despite interventions, the patient’s condition deteriorated, leading to the diagnosis of pulmonary metastasis and eventual death three months after the second surgery. This case highlights the need for increased awareness and accurate diagnosis of TOS, particularly in atypical presentations.